5-fluorouracil pharmacogenomics: still rocking after all these years?. (February 2011) - Scartozzi, Mario; Maccaroni, Elena; Giampieri, Riccardo; Pistelli, Mirco; Bittoni, Alessandro; Del Prete, Michela; Berardi, Rossana; Cascinu, Stefano
The 5-fluorouracil (5-FU) metabolic pathway is mainly dependent on the activity of several intracellular enzymes. Among them, four in particular; thymidylate synthase, methylenetetrahydrofolate reductase, dihydropyrimidine dehydrogenase and thymidine phosphorylase are considered the key points in determining sensitivity or resistance to this drug. These enzymes are needed to metabolize the drug in its active form (thymidylate phosphorylase) or to drop the concentration of the active drug in the cell (dihydropyrimidine dehydrogenase) or both (thymidylate synthase and methylenetetrahydrofolate reductase). Several different studies have tried to investigate the relationship between the presence of mutations in these enzymes and a reduced/improved activity of treatment based on 5-FU or its derivatives. In this article, we will focus on the often contradictory results of these studies.